Optimal Dispatch of Integrated Energy System Considering Operational Risks in the Presence of Energy Storage - Yunhui SHI; Chuangxin GUO (发电技术)
In order to solve the risk problem brought by uncertainties of supply and demand in integrated energy system (IES), an optimal dispatch model of IES with energy storage considering operational risk was proposed. In the objective function, the cost of equipment adjustment, penalty for loss of load and penalty for curtailment of wind and solar power was used to quantify the operational risk of the IES. In the constraints, the time-scale differences between electric energy and thermal energy were distinguished, and the multi-period coupling constraints of energy storage were established considering the time coupling of energy storage. Then an algorithm based on Benders decomposition was proposed to solve the problem. Finally, an example was given to analyze the influence of confidence level, energy storage power and capacity on IES operation cost and operational risk.